Full medical program fees and medical student career intention. Issue 1 (19th January 2015) - Hays, Richard B; Lockhart, Kathleen R; Teo, Edward; Smith, Janie; Waynforth, David
Abstract: Objective: To explore the future career preferences of Commonwealth‐supported place (CSP) and full‐fee paying (FFP) medical students in Australia. Design, setting and participants : Data from the Medical Schools Outcomes Database and Longitudinal Tracking (MSOD) Project exit questionnaire for CSP and FFP students who graduated between 2008 and 2011 were analysed using logistic regression. The influence of age, sex, marital status, rural background and fee‐paying status on future career preference were explored. Main outcome measure : Future career preference (location and specialty) at graduation. Results: Compared with CSP students, domestic FFP students were more likely to nominate as their first preference both urban locations (odds ratio [OR], 5.58; 95% CI, 2.04–15.26; P  < 0.001) and higher‐income specialties (OR, 1.37; 95% CI, 1.07–1.75; P  < 0.05), and less likely to nominate as their first preference in‐need specialties (OR, 0.72; 95% CI, 0.52–1.00; P  < 0.05), specifically general practice (OR, 0.71; 95% CI, 0.52–0.99; P  < 0.05). There was a significant domestic FFP student by marital status interaction effect, such that domestic FFP students who were married or partnered on exit from medical school were more likely to prefer a rural location (OR, 0.64; 95% CI, 0.44–0.95; P  < 0.05). Also, students who were married or partnered were less likely to select a one of the higher‐income specialties as their first preference (OR, 0.77; 95% CI, 0.64–0.92; P  < 0.01). A rural background increased preferences for rural location (OR, 0.18; 95% CI, 0.15–0.22; P  < 0.001) and in‐need specialties (OR, 1.28; 95% CI, 1.04–1.57; P  < 0.05), and being older on entry to medical school also increased preferences for rural location (OR, 0.96; 95% CI, 0.95–0.98; P  < 0.001) and in‐need specialties (OR, 1.03; 95% CI, 1.01–1.04; P  < 0.01). International FFP students were more likely to prefer urban practice (OR, 1.79; 95% CI, 1.19–2.72; P  < 0.01). Conclusion: Domestic FFP graduates are less likely to prefer careers in rural locations and in lower‐paid and in‐need specialties, particularly general practice. Current workforce implications might be minor, but if fees for CSP students increase or more FFP places become available, potential impacts on workforce distribution will need to be considered.